Pseudo-boehmite and preparation method thereof
By using mercaptopropionic acid-modified ZnS quantum dots and a composite pore-directing agent to control the pore size distribution of pseudoboehmite, the problem of uneven pore size distribution in the prior art is solved, and the preparation of a highly efficient catalyst support is achieved, which is suitable for fine chemical catalytic reactions.
Patent Information
- Application Number
- CN202511666126.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-11-14
- Publication Date
- 2025-12-12
- Estimated Expiration
- 2045-11-14
AI Technical Summary
The existing pseudoboehmite has a wide and excessively large pore size distribution, which leads to reduced dispersion of active components and ineffective consumption of reactant diffusion pathways in fine chemical catalytic reactions, making it difficult to meet the catalytic efficiency requirements of reactions such as olefin epoxidation and aromatic hydroxylation.
Using mercaptopropionic acid-modified ZnS quantum dots as crystal form regulators, combined with a composite pore size guiding agent of polyethylene glycol-polypropylene glycol-polyethylene glycol triblock copolymer and sodium citrate, pseudoboehmite with a mesopore ratio of 5-10 nm and more than 90% was prepared by controlling pH, temperature and stirring rate, ensuring that the crystal nuclei grow along a specific crystal plane and restricting pore expansion.
It achieves a concentrated distribution of mesopore size in pseudoboehmite, improving the dispersion of active components and the diffusion efficiency of reactants. It is suitable for fine chemical reactions such as olefin epoxidation and aromatic hydroxylation, and significantly improves the selectivity and efficiency of catalysts.
Smart Images

Figure CN121107443A_ABST
Abstract
Description
Technical Field
[0001] This application relates to the field of inorganic material preparation, and more specifically, to a pseudoboehmite and its preparation method. Background Technology
[0002] Alumina, due to its excellent physicochemical properties, is used as a carrier material in various chemical fields, especially as a hydrogenation catalyst in petroleum processing. The main raw material for producing alumina carriers is boehmite (AlOOH·nH2O, n = 0.08–0.62), also known as pseudoboehmite, a type of aluminum hydroxide with uncertain composition, incomplete crystallization, and thin, wrinkled lamellar layers, characterized by high specific surface area and large pore volume. The performance of alumina carriers is mainly determined by the properties of its precursor, boehmite, particularly its pore structure. Therefore, to prepare high-performance alumina carriers, it is essential to first obtain high-performance boehmite fractions. Industrially, the main methods for preparing boehmite include neutralization, seeding, and aluminum alkoxide methods. Neutralization is currently the most commonly used method in China, and it can be further subdivided into aluminum nitrate method, aluminum sulfate method, carbonization method, double aluminum method, and pH swing method.
[0003] In related technologies, such as patent publication number CN116253344B, a pseudoboehmite and its preparation method, as well as the alumina obtained therefrom, are disclosed. In this method, the pseudoboehmite is prepared using a double-aluminum method, which involves mixing an aluminum salt solution with an aluminate solution containing inorganic additives, allowing it to nucleate and age to obtain pseudoboehmite. The prepared pseudoboehmite has a pore volume of 0.5-2.0 cm³. 3 / g, but the pore size is mainly concentrated in 15-32nm. Although the pseudoboehmite prepared by this method has certain advantages in pore volume and specific surface area, the pore size distribution range is wide and concentrated in a large mesoporous region.
[0004] However, since the pore size of the aforementioned boehmite is mainly concentrated in the 15-32 nm range, for boehmite used as a catalyst support in fine chemical reactions such as olefin epoxidation and aromatic hydroxylation, the reactants are mostly small-molecule organic compounds such as propylene and phenol, with molecular dynamic diameters of approximately 0.3-0.8 nm. Furthermore, the reactions require rapid adsorption and conversion at the catalyst's active sites. A wide pore size distribution and excessively large pores would lead to reduced dispersion of active components and increased ineffective consumption of reactant diffusion pathways, thus reducing catalytic efficiency. Therefore, for boehmite used as a catalyst support in reactions such as olefin epoxidation and aromatic hydroxylation, a highly concentrated mesopore size distribution is required, particularly with pores of 5-10 nm accounting for over 90%. This ensures good dispersion of active components and reactant diffusion selectivity in catalyst applications. However, the boehmite in related technologies, due to its large and dispersed pore size, cannot meet these requirements, limiting its support performance in such fine catalytic reactions and hindering the achievement of high-efficiency catalysis. Summary of the Invention
[0005] In order to prepare boehmite with a pore size of 5-10 nm accounting for more than 90% and thus meet the pore distribution requirements of boehmite for fine catalytic reactions and achieve efficient catalysis, this application provides a boehmite and its preparation method.
[0006] The technical solution provided in this application for a pseudoboehmite and its preparation method is as follows: A method for preparing pseudoboehmite includes the following steps: (1) After mixing aluminum salt solution and aluminate solution, add crystal form regulator, adjust the pH of the reaction system to 7.5-8.5 by pH regulator, the reaction temperature to 50-65℃, the stirring rate to 200-300r / min, and the reaction to obtain sol system after 1-2h; the crystal form regulator is mercaptopropionic acid modified ZnS quantum dots; (2) Add a pore size guiding agent to the sol system and age it at 45-55℃ for 6-8 hours, continuously purging inert gas for protection during the aging process; the pore size guiding agent is a compound of polyethylene glycol-polypropylene glycol-polyethylene glycol triblock copolymer and sodium citrate; (3) The aged sol system was subjected to solid-liquid separation, and the resulting solid was washed and dried to obtain boehmite.
[0007] By adopting the above technical solution, after the surface of ZnS quantum dots in the crystal form regulator is modified with mercaptopropionic acid (HS-CH2CH2COOH), the mercapto groups (-SH) can react with aluminum ions (Al). 3+ Coordinate bonds are formed, and the negative charge generated from the dissociation of carboxyl groups on the surface of the quantum dot is used to directionally adsorb Al through electrostatic interactions. 3+The pseudoboehmite nuclei preferentially grow along the (001) crystal plane. This crystal plane has a layered structure with an interlayer distance of about 0.7-0.8 nm. The mesopore channels formed by the interlayer stacking fall exactly in the 5-10 nm range. By coordinating the number of interlayer stackings with the quantum dot size, the generation of macropores is restricted from the root of the crystal structure, so that the mesopores of the crystal are concentrated in 5-10 nm for growth. The PEG segments of the PEG-PPG-PEG triblock copolymer in the pore size guiding agent can be anchored to the surface of the pseudoboehmite nuclei by hydrogen bonds to form a "spatial template" to restrict the pore expansion during the lateral growth of the nuclei; the PPG segments (hydrophobic tail chains) repel each other to avoid the pore size unevenness caused by template aggregation, which is conducive to promoting the growth of the mesopores of the crystal concentrated in 5-10 nm and continuous growth along the (001) crystal plane. The citrate ions (C6H5O7) ionized from sodium citrate 3- ) and Al 3+ Weak coordination is formed, which stabilizes the crystal nucleus dispersion through electrostatic repulsion, prevents particle agglomeration and the formation of large pore defects, and simultaneously inhibits Al 3+ The disordered porous structure is caused by excessively rapid hydrolysis. The pH of the reaction system in step (1) is controlled to be 7.0-8.5, and the reaction temperature to be 50-65℃, thereby controlling the Al... 3+ The hydrolysis rate makes Al under weakly alkaline conditions 3+ Slowly generating the AlOOH precursor avoids pore structure disruption caused by rapid precipitation; 50-65℃ promotes the reaction of quantum dots with Al. 3+ The coordination reaction improves the crystal structure guiding efficiency. In step (2), aging under inert gas protection can prevent dissolved oxygen in the solution from oxidizing the quantum dot surface groups, maintain their coordination activity, and ensure the continuity of directional growth of crystal nuclei. The preparation method of this application ensures the fundamental stability of the pore structure through crystal structure regulation, limits the pore size range by using a pore size guiding agent, and controls the process parameters to avoid impurity interference, ultimately achieving the goal of high proportion of concentrated mesopores. The pore ratio of 5-10 nm of the prepared pseudoboehmite reaches more than 90%, which can meet the pore distribution requirements of pseudoboehmite for fine catalytic reactions and is conducive to achieving efficient catalysis.
[0008] Optionally, the concentration of the aluminum salt solution is 0.8-1.2 mol / L; the aluminum salt solution is any one of aluminum nitrate solution, aluminum chloride solution, and aluminum sulfate.
[0009] Optionally, in step (1), the aluminate solution is a sodium aluminate solution; the concentration of the sodium aluminate solution is 0.9-1.1 mol / L.
[0010] By adopting the above technical solution, the type, concentration, and ratio of the above aluminum salts and aluminates are ensured to guarantee Al 3+ With AlO2 -The neutralization reaction rate is stable, providing a suitable aluminum ion concentration environment for the crystal form regulator and pore size guide to function, avoiding pore size deviations caused by fluctuations in raw material concentration. The volume ratio of aluminum salt to aluminate can control the Al content. 3+ With AlO2 - The reaction amount is controlled to ensure a stable stoichiometric ratio of AlOOH produced and to avoid excess Al. 3+ or AlO2 - The resulting amorphous impurities ensure the uniformity of crystal nucleus growth, thereby ensuring the stability of mesopore size.
[0011] Optionally, in step (1), the volume ratio of the aluminum salt solution to the aluminate solution is (0.8-1.2):1; the amount of the crystal form regulator added is 2%-4% of the total mass of the aluminum salt solution and the aluminate solution.
[0012] By adopting the above technical solution, the amount of crystal form regulator added can effectively cover the surface of the crystal nucleus of pseudoboehmite, which not only avoids insufficient guidance due to insufficient dosage, but also prevents excessive quantum dots from agglomerating into impurity cores, which is conducive to ensuring the stability of the pore size distribution of pseudoboehmite and the purity of the product.
[0013] Optionally, the crystal form regulator is prepared by the following method: A. Mix ZnS quantum dot dispersion with mercaptopropionic acid aqueous solution, add phosphate buffer solution to adjust pH to 7.0-8.0, and shake the reaction at 35-45℃ for 1.5-2.5h to obtain mercaptopropionic acid modified ZnS quantum dot dispersion; B. After dialysis purification, the dispersion obtained in step A is freeze-dried to obtain the crystal form regulator.
[0014] By adopting the above technical solution, in step A, by covering the surface of the quantum dots with mercaptopropionic acid, the mercapto groups react with Zn. 2+ The coordination constant is higher than that of the Zn-S bond, enabling surface modification and substitution. The dissociation of the carboxyl group provides a stable negative charge site. Oscillatory reactions promote molecular diffusion, ensuring uniform modification. Dialysis purification removes unreacted mercaptopropionic acid, preventing its reaction with Al. 3+ Non-specific binding interferes with crystal nucleus growth. Through the above preparation method, it is ensured that the ZnS quantum dot surface is sufficiently modified and well dispersed, thereby stably exerting the crystal form guiding effect and avoiding the failure of pore size control due to insufficient quantum dot modification.
[0015] Optionally, the ZnS quantum dot dispersion has a mass concentration of 8%-12%, the mercaptopropionic acid aqueous solution has a mass concentration of 5%-8%, and the mass ratio of the ZnS quantum dot dispersion to the mercaptopropionic acid aqueous solution is 1:(4-6).
[0016] Optionally, in step (2), the mass ratio of polyethylene glycol-polypropylene glycol-polyethylene glycol triblock copolymer to sodium citrate in the pore size guiding agent is (3-5):1; the amount of the pore size guiding agent added is 1.5%-3% of the mass of the sol system.
[0017] Optionally, in step (3), the washing is performed using a mixture of deionized water and ethanol, with a volume ratio of deionized water to ethanol of (2-3):1, and the washing is performed until the conductivity of the filtrate is ≤50μS / cm; the solid drying temperature is 40-50℃ and the drying time is 10-12h.
[0018] Optionally, the polyethylene glycol-polypropylene glycol-polyethylene glycol triblock copolymer has a molecular weight of 2000-3000, wherein the polyethylene glycol segment accounts for 60%-70%, and the hydroxyl value is 15-10mg.
[0019] By adopting the above technical solution, and by limiting the pore size guiding agent to the above-mentioned compound ratio, molecular weight and chain segment ratio, the proportion of 5-10nm pore size can be precisely controlled, avoiding pore size fluctuations caused by a single template agent.
[0020] This application also provides a pseudoboehmite, prepared using the above-described method, wherein the pore size distribution of the pseudoboehmite has a pore size distribution in the 5-10 nm range with a pore size ratio >90%, and the pore volume of the pseudoboehmite is >1.9 cm³. 3 / g.
[0021] The pseudoboehmite prepared by the above-described method in this application has a mesopore size of ≥90% in the 5-10 nm range, with a concentrated distribution of 5-10 nm pore size, effectively solving the problems of excessively large pore size and dispersed distribution in existing technologies. The high proportion of 5-10 nm mesopores perfectly matches the diffusion requirements of small molecule reactants in fine chemicals, reducing ineffective diffusion paths. Simultaneously, the pore confinement effect significantly improves the dispersion of active components, preventing material aggregation. Furthermore, this pseudoboehmite maintains a stable pore structure even after calcination, providing a continuously efficient active environment for catalytic reactions. It is particularly suitable as a catalyst support for fine chemical reactions such as olefin epoxidation and aromatic hydroxylation, significantly improving reaction selectivity and efficiency. It also has broad application prospects in environmental catalysis, new energy materials, and other fields, meeting the stringent requirements for support pore structure in various scenarios.
[0022] In summary, this application has the following beneficial effects: 1. In the preparation process of boehmite in this application, mercaptopropionic acid-modified ZnS quantum dots are used as crystal structure regulators. The mercapto groups on their surface form coordination bonds with aluminum ions, and the negative charge of the dissociated carboxyl groups directionally adsorbs aluminum ions through electrostatic interaction, inducing the preferential growth of crystal nuclei along the (001) crystal plane. The interlayer distance of this crystal plane is about 0.7-0.8 nm, and the mesoporous channels formed by the interlayer stacking naturally fall within the 5-10 nm range, thus limiting the formation of macropores from the root of the crystal structure. At the same time, the pore size guiding agent, which is a combination of polyethylene glycol-polypropylene glycol-polyethylene glycol triblock copolymer and sodium citrate, restricts the pore expansion of the lateral growth of crystal nuclei through the "spatial template" effect, and stabilizes the dispersion of crystal nuclei with electrostatic repulsion, avoiding the formation of macropore defects by particle agglomeration. With the synergistic control of process parameters such as pH, temperature, and stirring rate, the proportion of pores with a diameter of 5-10 nm in boehmite reaches more than 90%, solving the problems of large pore size and dispersed distribution in the prior art.
[0023] 2. The high proportion of 5-10 nm mesopores in the pseudoboehmite prepared in this application perfectly matches the diffusion requirements of small molecule reactants in fine chemicals, reducing ineffective diffusion paths. Simultaneously, the pore confinement effect significantly improves the dispersion of active components, preventing material aggregation. Furthermore, this pseudoboehmite maintains a stable pore structure even after calcination, providing a continuous and efficient active environment for catalytic reactions. It is particularly suitable as a catalyst support for fine chemical reactions such as olefin epoxidation and aromatic hydroxylation, significantly improving reaction selectivity and efficiency. Attached Figure Description
[0024] Figure 1 This is a graph showing the changes in pore size and pore volume of the pseudoboehmite in Example 1 of this application. Figure 2 This is a graph showing the changes in pore size and pore volume of the pseudoboehmite in Comparative Example 1 of this application. Detailed Implementation
[0025] The present application will be further described in detail below with reference to the embodiments.
[0026] Preparation example of crystal form regulator Preparation Example 1 The crystal form regulator was prepared by the following method: A. Mix 1 kg of 8% ZnS quantum dot dispersion with 4 kg of 5% mercaptopropionic acid aqueous solution, add phosphate buffer solution to adjust pH to 7.0, and shake the reaction at 35℃ for 1.5 h to obtain mercaptopropionic acid modified ZnS quantum dot dispersion. B. The dispersion obtained in step A is purified by dialysis. The dispersion is dialyzed with deionized water at 30°C for 12 hours. The purified solution is then freeze-dried to obtain the crystal form regulator.
[0027] Preparation Example 2 The crystal form regulator was prepared by the following method: A. Mix 1 kg of 10% ZnS quantum dot dispersion with 5 kg of 6% mercaptopropionic acid aqueous solution, add phosphate buffer solution to adjust pH to 7.5, and shake the reaction at 40℃ for 2.0 h to obtain mercaptopropionic acid modified ZnS quantum dot dispersion. B. The dispersion obtained in step A is purified by dialysis. The dispersion is dialyzed with deionized water at 30°C for 12 hours. The purified solution is then freeze-dried to obtain the crystal form regulator.
[0028] Preparation Example 3 The crystal form regulator was prepared by the following method: A. Mix 1 kg of ZnS quantum dot dispersion with a mass concentration of 12% with 6 kg of mercaptopropionic acid aqueous solution with a mass concentration of 8%, add phosphate buffer solution to adjust the pH to 8.0, and shake the reaction at 45℃ for 2.5 h to obtain mercaptopropionic acid modified ZnS quantum dot dispersion. B. The dispersion obtained in step A is purified by dialysis. The dispersion is dialyzed with deionized water at 30°C for 12 hours. The purified solution is then freeze-dried to obtain the crystal form regulator.
[0029] Preparation Example 4 The crystal form regulator differs from that in Preparation Example 1 in that the mass concentration of the ZnS quantum dot dispersion in this preparation example is 20%.
[0030] Example Example 1 A method for preparing pseudoboehmite includes the following steps: (1) 4L of 0.8mol / L aluminum nitrate solution and 5L of 0.9mol / L sodium aluminate solution were mixed and 180g of the crystal form regulator prepared in Example 1 was added. The pH of the reaction system was adjusted to 7.5 by using 20% sodium hydroxide solution. The reaction temperature was 50℃ and the stirring rate was 200r / min. After reacting for 1h, a sol system was obtained. (2) Add 138g of pore-directing agent to the sol system and age it at 45°C for 6 hours. Nitrogen gas is continuously introduced for protection during the aging process. The pore-directing agent is a compound of polyethylene glycol-polypropylene glycol-polyethylene glycol triblock copolymer and sodium citrate in a mass ratio of 3:1. (3) The aged sol system was centrifuged and the resulting solid was washed with a mixture of deionized water and ethanol at a volume ratio of 2:1 until the conductivity of the filtrate was ≤50μS / cm. Then, it was vacuum dried at 40℃ for 10h to obtain boehmite.
[0031] Example 2 A method for preparing pseudoboehmite includes the following steps: (1) Mix 5L of 1.0mol / L aluminum chloride solution and 5L of 1.0mol / L sodium aluminate solution, then add 300g of the crystal form regulator prepared in Example 2. Adjust the pH of the reaction system to 8.0 with 20% sodium hydroxide solution, set the reaction temperature to 60℃, and the stirring rate to 250r / min. After reacting for 1.5h, a sol system is obtained. (2) Add 260g of pore size guiding agent to the sol system and age it at 50℃ for 7h. Nitrogen gas is continuously introduced for protection during the aging process. The pore size guiding agent is a compound of polyethylene glycol-polypropylene glycol-polyethylene glycol triblock copolymer and sodium citrate in a mass ratio of 4:1. (3) The aged sol system was centrifuged and the resulting solid was washed with a mixture of deionized water and ethanol at a volume ratio of 2.5:1 until the conductivity of the filtrate was ≤50μS / cm. Then, it was vacuum dried at 45℃ for 11h to obtain boehmite.
[0032] Example 3 A method for preparing pseudoboehmite includes the following steps: (1) 6 L of 1.2 mol / L aluminum sulfate solution and 5 L of 1.1 mol / L sodium aluminate solution were mixed and 440 g of the crystal form regulator prepared in Example 3 was added. The pH of the reaction system was adjusted to 8.5 by using 20% sodium hydroxide solution. The reaction temperature was 65 °C and the stirring rate was 300 r / min. After 2 h of reaction, a sol system was obtained. (2) Add 345g of pore size guiding agent to the sol system and age it at 55℃ for 8h. Nitrogen gas is continuously introduced for protection during the aging process. The pore size guiding agent is a compound of polyethylene glycol-polypropylene glycol-polyethylene glycol triblock copolymer and sodium citrate in a mass ratio of 5:1. (3) The aged sol system was centrifuged and the resulting solid was washed with a mixture of deionized water and ethanol at a volume ratio of 3:1 until the conductivity of the filtrate was ≤50μS / cm. Then, it was vacuum dried at 50℃ for 12h to obtain boehmite.
[0033] Example 4 A method for preparing pseudoboehmite differs from Example 1 in that the crystal form regulator used in this example is the crystal form regulator prepared in Preparation Example 4.
[0034] Example 5 A method for preparing pseudoboehmite differs from Example 1 in that the pore guiding agent in this example is a compound of polyethylene glycol-polypropylene glycol-polyethylene glycol triblock copolymer and sodium citrate in a mass ratio of 1:1.
[0035] Comparative Example Comparative Example 1 The pseudoboehmite was prepared according to Example 3 in the patent document with publication number CN116253344B, entitled "A pseudoboehmite and its preparation method and the alumina obtained therefrom".
[0036] Comparative Example 2 A method for preparing pseudoboehmite differs from Example 1 in that no crystal form regulator is added in step (1) and no pore size guide is added in step (2) of this example, and the sol system is directly aged.
[0037] Comparative Example 3 A method for preparing pseudoboehmite differs from Example 1 in that, in step (1) of this example, an equal amount of ZnS quantum dots are used instead of the crystal form regulator.
[0038] Comparative Example 4 A method for preparing pseudoboehmite differs from Example 1 in that, in step (2) of this example, an equal amount of polyethylene glycol-polypropylene glycol-polyethylene glycol triblock copolymer is used instead of the pore size guiding agent.
[0039] Performance testing The performance indicators of the pseudoboehmite prepared in Examples 1-5 and Comparative Examples 1-4 were tested, and the results are shown in Table 1.
[0040] Table 1 Test Results
[0041] As shown in Table 1, the specific surface area of the pseudoboehmite prepared in Examples 1-3 is 423-427 m². 2 / g, pore volume 1.95-1.97cm³ 3 The / g indicates that the pseudoboehmite prepared in this application has a high specific surface area and pore volume. A larger specific surface area provides more active sites for the catalytic reaction, and a larger pore volume facilitates the diffusion and transport of reactants and products, thereby improving the efficiency of the catalytic reaction. (Refer to...) Figure 1The peak pore sizes of the boehmite prepared in Examples 1-3 were 7.2 nm, 7.4 nm, and 7.2 nm, respectively, all concentrated in the 5-10 nm range, and the values were relatively stable. This indicates that the preparation method of this application, through the synergistic effect of crystal form regulators and pore size guiding agents, as well as the precise control of process parameters, can effectively control the pore size of boehmite within the ideal range; the pore volume ratio of 5-10 nm all reached over 95%. This demonstrates that the preparation method of this application can concentrate the mesopore height of boehmite in the 5-10 nm range, meeting the stringent requirements for boehmite pore distribution in fine chemical reactions such as olefin epoxidation and aromatic hydroxylation, which is beneficial for achieving efficient catalysis.
[0042] The peak pore size of the pseudoboehmite obtained in Example 4 was 9.5 nm, which, although still within the 5-10 nm range, was larger than that in Examples 1-3. This indicates that the ZnS quantum dot dispersion affects the performance of the crystal form regulator during preparation, thus making the pore size control unstable. This may lead to changes in the interlayer stacking during crystal nucleation, resulting in an increase in the peak pore size.
[0043] The peak pore size of the boehmite prepared in Example 5 was 10.3 nm, indicating a large number of mesopores larger than 10 nm. The volume fraction of 5-10 nm pores was 87.2%, which is lower than that in Examples 1-3. This shows that the formulation ratio of the guiding agent has a significant impact on the proportion of 5-10 nm pores, further emphasizing the importance of precisely controlling the formulation ratio of the pore size guiding agent.
[0044] The peak pore size of the boehmite prepared in Comparative Example 1 was 32.3 nm, which is much larger than the ideal range of 5-10 nm. The pore size of the boehmite prepared by this method is mainly concentrated in the 15-32 nm range, which cannot meet the requirements for small pore size in fine catalytic reactions. The 5-10 nm pore volume accounts for only 35.6%, far lower than the level in the embodiments of this application. This fully demonstrates that the boehmite in related technologies, due to its large pore size and dispersed distribution, has limited support performance in such fine catalytic reactions, making it difficult to achieve efficient catalysis.
[0045] The 5-10 nm pore volume ratio of the pseudoboehmite prepared in Comparative Example 2 was only 42.3%, far lower than that in the Example. This indicates that crystal form regulators and pore size guiding agents play crucial roles in controlling pore size distribution and increasing the 5-10 nm pore volume ratio, and neither can be omitted.
[0046] The 5-10 nm pore volume ratio of the pseudoboehmite prepared in Comparative Example 3 was 65.6%, which was higher than that in Comparative Examples 1 and 2, but much lower than that in the Example. This further demonstrates the importance of mercaptopropionic acid modification for ZnS quantum dots as crystal form regulators. It is difficult to effectively control the mesopore size using ZnS quantum dots alone. Only appropriately modified quantum dots can effectively play a crystal form guiding role, thereby increasing the proportion of 5-10 nm pores.
[0047] The 5-10 nm pore volume ratio of the pseudoboehmite prepared in Comparative Example 4 was 65.2%, similar to Comparative Example 3, but much lower than that in the Example. This indicates that the combination of polyethylene glycol-polypropylene glycol-polyethylene glycol triblock copolymer and sodium citrate in the pore size guiding agent is necessary, and their synergistic effect is required to better achieve precise control of pore size and increase the proportion of 5-10 nm pores.
[0048] This specific embodiment is merely an explanation of this application and is not intended to limit it. After reading this specification, those skilled in the art can make modifications to this embodiment without contributing any inventive step, but such modifications are protected by patent law as long as they fall within the scope of the claims of this application.
Claims
1. A method for preparing pseudoboehmite, characterized in that, The steps include the following: (1) After mixing aluminum salt solution and aluminate solution, add crystal form regulator, adjust the pH of the reaction system to 7.5-8.5 by pH regulator, the reaction temperature to 50-65℃, the stirring rate to 200-300r / min, and the reaction to obtain sol system after 1-2h; the crystal form regulator is mercaptopropionic acid modified ZnS quantum dots; (2) Add a pore size guiding agent to the sol system and age it at 45-55℃ for 6-8 hours, continuously purging inert gas for protection during the aging process; the pore size guiding agent is a compound of polyethylene glycol-polypropylene glycol-polyethylene glycol triblock copolymer and sodium citrate; (3) The aged sol system was subjected to solid-liquid separation, and the resulting solid was washed and dried to obtain boehmite.
2. The method for preparing pseudoboehmite according to claim 1, characterized in that: The concentration of the aluminum salt solution is 0.8-1.2 mol / L; the aluminum salt solution is any one of aluminum nitrate solution, aluminum chloride solution, and aluminum sulfate.
3. The method for preparing pseudoboehmite according to claim 2, characterized in that: In step (1), the aluminate solution is a sodium aluminate solution; the concentration of the sodium aluminate solution is 0.9-1.1 mol / L.
4. The method for preparing pseudoboehmite according to claim 3, characterized in that: In step (1), the volume ratio of the aluminum salt solution to the aluminate solution is (0.8-1.2):1; the amount of the crystal form regulator added is 2%-4% of the total mass of the aluminum salt solution and the aluminate solution.
5. The method for preparing pseudoboehmite according to claim 4, characterized in that, The crystal form regulator is prepared by the following method: A. Mix ZnS quantum dot dispersion with mercaptopropionic acid aqueous solution, add phosphate buffer solution to adjust pH to 7.0-8.0, and shake the reaction at 35-45℃ for 1.5-2.5h to obtain mercaptopropionic acid modified ZnS quantum dot dispersion; B. After dialysis purification, the dispersion obtained in step A is freeze-dried to obtain the crystal form regulator.
6. The method for preparing pseudoboehmite according to claim 5, characterized in that: The ZnS quantum dot dispersion has a mass concentration of 8%-12%, the mercaptopropionic acid aqueous solution has a mass concentration of 5%-8%, and the mass ratio of the ZnS quantum dot dispersion to the mercaptopropionic acid aqueous solution is 1:(4-6).
7. The method for preparing pseudoboehmite according to claim 1, characterized in that: In step (2), the mass ratio of polyethylene glycol-polypropylene glycol-polyethylene glycol triblock copolymer to sodium citrate in the pore size guiding agent is (3-5):1; the amount of the pore size guiding agent added is 1.5%-3% of the mass of the sol system.
8. The method for preparing pseudoboehmite according to claim 1, characterized in that, In step (3), the washing process uses a mixture of deionized water and ethanol, with a volume ratio of deionized water to ethanol of (2-3):
1. The washing is carried out until the conductivity of the filtrate is ≤50μS / cm. The solid drying temperature is 40-50℃ and the drying time is 10-12h.
9. The method for preparing pseudoboehmite according to claim 7, characterized in that, The polyethylene glycol-polypropylene glycol-polyethylene glycol triblock copolymer has a molecular weight of 2000-3000, wherein the polyethylene glycol segment accounts for 60%-70% and the hydroxyl value is 15-10mg.
10. A pseudoboehmite, characterized in that, The pseudoboehmite, prepared by the method according to any one of claims 1-9, has a pore size distribution in which pores of 5-10 nm account for >90%, and a pore volume of >1.9 cm³. 3 / g.
Citation Information
Patent Citations
Pseudo-boehmite, preparation method thereof and aluminum oxide prepared therefrom
CN116253344B
Quantum dot composite material, preparation method thereof and quantum dot light-emitting diode
CN113122233A
Method for improving pore volume and pore diameter of pseudo-boehmite
CN115180642A
Pseudo-boehmite, preparation method thereof and gamma-alumina carrier with high diffusion mass transfer performance
CN119612563A
Preparation method of double-peak pore tooth spherical alumina carrier
CN120189930A
Cited By
Pseudo-boehmite and preparation method thereof
CN122324840A